Comparative developmental physiology : contributions, tools, and trends - Warburton, Stephen J. (Oxford University Press, 2006)
Presents assessments of work in the field of developmental physiology from experimental, theoretical, and molecular perspectives. This work provides an overview of an area, which is relevant to the research of physiologists, ecologists, evolutionary biologists, and developmental biologists.